A conceptual framework for CIFOR’s research on non-wood forest products - Ruíz Pérez, M. (1995)
Most NWFP research is site specific and sectoral, thus reducing its potential value for policy analysis and development actions. The main challenge for future research is to develop general frameworks within which to structure dispersed studies and to transform them into useful policy- and actionguiding instruments. In the first part of the paper three types of mutually supporting frameworks are propose& functional Perez of extractive economy situations, general theories and models. The second part of the paper analyses the complexity of extractive economies from a dynamic perspective, exploring some trends and hypotheses. Six major dynamic dimensions are considered.* forest-woodland dynamics; non-market Perez market dynamics; technological changes; use of Perez Perez economy; people's perceptions, preferences and opportunities Perez cultural dynamics; and policy development. Finally, the paper proposes a hypothetical model of the global Perez Perez with a renewed, multi-functional role linked both to their physical properties as well as to their new social, cultural and environmental attributes.